Cardioprotective efficacy of Ficus deltoidea Jack against carbon tetrachloride-induced damage and hyperlipidemia in rats / Fatima Uzar - Fatima , Uzar (2015)
The purpose of this study was to evaluate the effects of Ficus deltoidea leaf extracts on carbon tetrachloride (CCl4)-induced myocardial infarction (MI) and diet-induced hyperlipidemia in rats. Water fraction, ethanolic, and water extracts were prepared, and their in-vitro antioxidant capacity was tested using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and Cupric ion Reducing Antioxidant Capacity (CUPRAC) assays. The total phenolic content (TPC) was measured using Folin–Ciocalteau assay, and the ability of the extract to inhibit the lipid oxidation was tested using lipid peroxidation assay. Finally, hydroxymethylglutaryl-coenzymeA (HMG-CoA) reductase assay was conducted in-vitro to evaluate the inhibition of cholesterol biosynthesis. The three extracts exhibited a significant antioxidant and cholesterol lowering activity in-vitro, with the ethanol extract showing comparatively better activity. In a study to determine the efficacy of F. deltoidea ethanol extract as a cardioprotective agent, rats were pre-treated with ethanol extract followed by CCl4 to induce MI. Meanwhile, to evaluate the capability of F. deltoidea extracts as anti-atherogenic agent, rats were given daily treatment of the extract along with high-fat diet to induce hyperlipidemia. Cardiac tissue marker enzymes, lipid profile, inflammation rate and NADP concentration (as an indicator of oxidative stress) assays were conducted, both in tissue and serum samples. Finally, histopathology of the heart tissue was also carried out. In-vivo assays indicated a higher value of cardiac tissue marker enzymes and lipid profile components in CCl4- and high fat diet-induced rat groups compared to rats treated with the ethanol extract. The inflammation rate and oxidative stress (NADP concentration) were found to be higher in induced rats as compared to treated rats. Finally, the histopathology of induced rats showed visible necrosis to the heart tissue as compared to little or no damage to treated rat’s tissue. Thus, F. deltoidea extracts can be further researched as a potential cardioprotective natural compound.